2016
DOI: 10.1007/s12975-016-0508-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Cerebral Collateral Circulation

Abstract: Premenopausal women and intact female rodents sustain smaller cerebral infarctions than males. Several sex-dependent differences have been identified as potential contributors, but many questions remain unanswered. Mice exhibit wide variation in native collateral number and diameter (collateral extent) that is dependent on differences in genetic background, aging, and other comorbidities and that contributes to their also-wide differences in infarct volume. Likewise, variation in infarct volume correlates with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 71 publications
6
52
1
Order By: Relevance
“…Here, we found that a substantial difference in vascularization and bifurcation density exists across the regions of the Allen brain atlas. Furthermore, we found that intracranial anastomoses between the anterior cerebral artery, middle cerebral artery and the posterior cerebral artery which are known from C57BL/6J 35,47 , are also present in albino CD1-Elite strain. This is opposed to the BALB/c albino mouse where the absence of collaterals has been described 35 .…”
Section: Figure 6: Exemplary Quantitative Analysis Enabled By Vessapmentioning
confidence: 77%
“…Here, we found that a substantial difference in vascularization and bifurcation density exists across the regions of the Allen brain atlas. Furthermore, we found that intracranial anastomoses between the anterior cerebral artery, middle cerebral artery and the posterior cerebral artery which are known from C57BL/6J 35,47 , are also present in albino CD1-Elite strain. This is opposed to the BALB/c albino mouse where the absence of collaterals has been described 35 .…”
Section: Figure 6: Exemplary Quantitative Analysis Enabled By Vessapmentioning
confidence: 77%
“…In the cerebrovasculature, sex differences have been described with respect to vascular anatomy [21] and also pharmacology [60]. In the brain, arteriolar responses to vasoactive compounds, including angiotensin [19, 114] and endothelin-1 [29, 71], and nitric oxide synthase activity [88, 115], are sexually dimorphic.…”
Section: Vascular Reactivity (Vsm Dilation/constriction)mentioning
confidence: 99%
“…The incidence of stroke is higher in women than men, especially later in life [14, 21, 61, 99]. As with coronary microvessels, age and sex are significant, independent variables influencing cerebrovascular function.…”
Section: Vascular Reactivity (Vsm Dilation/constriction)mentioning
confidence: 99%
“…The basal level of cerebral collateralization as well as collateral remodeling after an ischemic insult greatly alters the ischemic outcomes. It is worth mentioning that the extent of the pial collateral formation differs among different strains as well as different pathological conditions but there is no sex effect (87, 262). …”
Section: Cerebrovascular Structurementioning
confidence: 99%